Densidade de estocagem em camarões da espécie Macrobrachium rosenbergii (De Man, 1879) na fase juvenil - Costa, Jamilly de Souza (2014)
Among the species of freshwater shrimp being cultivated, Macrobrachium rosenbergii stands out. Knowledge about the behavior of this species and the influence of certain factors on its development can help optimize management practices and minimize the likely impacts shrimp farming has on the environment and the animals themselves. The objective of this study was to characterize the species' behavior during early stages of development under different stocking densities over a 24-hour cycle. Ten day old postlarvae were transferred from the Jundiaí School of Agriculture (EAJ - Escola Agrícola de Jundiaí) in Macaíba (RN), Brazil to the Shrimp Behavior Laboratory (LSPR - Laboratório de Estudos do Comportamento do Camarão) at the Federal University of Rio Grande do Norte (UFRN), where they were weighed and measured. Eight aquaria with constant temperature, aeration and filtration, and subjected to a12 h light/12 h dark cycle were used for each experiment. Each aquarium also contained two shelters made of bricks and the water quality was monitored weekly. Behavioral observations were made at two densities: 25 individuals/m-² and 40 individuals/m-². The methods for recording behaviors were: behavioral sampling – enter and leave the shelter, exploring on the substrate, exploring in the water column, move away, attack, pursuit and cannibalism; scan sampling - inactivity, feeding, exploration, digging, swimming, cleaning and staying in the shelter. Observations were made during a 15 minute period/per aquarium at a frequency of 4 times daily, for 4 days/week, and over 4 weeks. Food was provided 2 times/day for each aquarium population, immediately before the 1st and 3rd observation periods. Our results demonstrate that at high density, there is an increased frequency of agonistic behavior; during the light phase, there is a greater frequency of behaviors that result in less exposure (inactivity, cleaning and staying in the shelter); during the dark phase, there is an increased frequency of behaviors that result in greater exposure (feeding, exploration, swimming and digging); at times of feed offer, there is an increased frequency of leaving the shelter, moving away, pursuit, feeding, exploration and swimming. At low density, the animals showed a lower frequency of agonistic behaviors, greater weight gain and higher growth rates, which indicates that this is a more favorable growing environment for cultivation and when applied, can generate better living conditions, favor survival rates and increase management success